Implementation of population screening for colorectal cancer by repeated fecal occult blood test in the Netherlands - Denters, Maaike J (BioMed Central, 2009)
BACKGROUND: Colorectal cancer (CRC) is the third most prevalent type of cancer in the world. Its prognosis is closely related to the disease stage at the time of diagnosis. Early detection of symptomless CRC or precursor lesions through population screening could reduce CRC mortality. However, screening programs are only effective if enough people are willing to participate. This study aims to asses the uptake of a second round of fecal occult blood test (FOBt) based screening and to explore factors that could potentially increase this uptake. METHODS AND DESIGN: Two years after the first screening round, 10.000 average risk persons, aged 50 to 75, will again receive an invitation to participate in immunohistochemical FOBt (iFOBt) based screening. Eligible persons will be recruited through a city population database. Invitees will be randomized to receive either an iFOBt with a faeces collection paper or an iFOBt without a collection paper. The iFOBts will be analyzed in a specialized laboratory at the Academic Medical Centre. Positive iFOBts will be followed by a consultation at our outpatient clinic and, in the absence of contra-indications and after informed consent, by a colonoscopy. The primary outcome measure is the participation rate. Secondary outcome measures are the effect of the addition of a collection paper on the participation rate, reasons for participation and non-participation, measures of informed choice and psychological consequences of screening and measures of psychological and physical burden associated with the iFOBt and the colonoscopy. Another secondary outcome measure is the diagnostic yield of the program. DISCUSSION: In order to implement population screening for colorectal cancer in the Netherlands, information is needed on the uptake of repeated rounds of FOBt-based screening and on factors that could potentially increase this uptake in the future since effectiveness of such a program depends on the willingness of persons to participate. This study will provide information on the actual uptake and perception of a second round of iFOBt-based screening. The results of this study will contribute to the future implementation of a national colorectal screening program in the Netherlands. TRIAL REGISTRATION: Dutch Trial register: NTR1327